Corporate corruption of South African politics and economics: ‘Accumulation by dispossession’ as a structural process, beyond ‘state capture’ - Bond, Patrick (New Agenda: South African Journal of Social and Economic Policy, 2024)
Author details: Patrick Bond is Distinguished Professor at the University of Johannesburg, Department of Sociology, where he is Director of the Centre for Social Change. From 2020-21 he was Professor at the Western Cape School of Government and from 2015-2019 was a Distinguished Professor of Political Economy at the University of the Witwatersrand School of Governance. From 2004 through mid-2016, he was Senior Professor at the University of KwaZulu-Natal School of Built Environment and Development Studies and was also Director of the Centre for Civil Society. He lectured from 1997-2004 at the Wits School of Governance. He has held visiting posts at a dozen universities and presented lectures at more than 100 others.